Gender and politeness on Instagram - Arini Dwi Sholikhatin; Rohmani Nur Indah (Department of Applied Linguistics, Graduate School of Universitas Negeri Yogyakarta, 2019)
This study is to identify the positive politeness of responses from male and female in responding to Bill Gates' caption on Instagram. It used a descriptive qualitative approach to explain the kind of positive politeness strategy applied. The data were in the form of positive utterances written by males and females in column comments in Bill Gates Instagram account analysed using Brown and Levinson’s theory of politeness. The data were collected on February, 2019, involving positive comments on Instagram. The results showed not all of the fifteen strategies of positive politeness appear. The strategy of noticing or attending to one’s interests and needs ranked the highest for the category of the most often appearing strategy used by males and females. The male’s comments tend to employ the strategy of joking about putting the hearer at ease and strategy of offering, promising. Whereas, the dominant positive politeness strategy used by females are noticing, attending to the hearer’s interests, wants, needs, or goods.